Effect of Fruit Iuices with Acetic Acid on the Quality and Storage Stability of Pickled Fish - Behanan, Lizy; Mathew, Saleena; D., Sudharma; M.K., Mukundan; V., Malika (Fishery Technology, 2025)
The results of pickling fish with fruit juices and acetic acid in comparison with acetic acid alone are reported. Tamarind juice, lime juice and gooseberry juice were tested for their pickling effect along with acetic acid. The biochemical and microbiological qualities of all the experimental samples remained good throughout the 6 months of study. The pickles prepared with tamarind juice along with acetic acid were superior to other pickles in colour, taste and texture. The pickle prepared using gooseberry juice and acetic acid was poor and unacceptable